Peningkatan Pengetahuan Masyarakat Mengenai Pentingnya Kesehatan Dalam Pemenuhan Gizi Keluarga di Desa Jetis, Bondowoso - Rusdi, Nabila Maulida; Aulia, Isthifa Annisa; Wahyu, Dahlia Tiara Trisnaning; Harun, Anindita Firma Aulia; Nabila, Nailun; Hasanah, Nur; Hidayah, Nurul; Puspito, Agung Nugroho; Ubaidillah, Mohammad; Isnainun, Ainaya; Sofwah, Ayaa; Arniyanti, Muslimah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Nutritional status is a determinant of the health of an individual or group as well as the wider community. In Indonesia, the problem of nutrition is still very high. This occurs due to a lack of interest in exploring information about healthy living and balanced nutrition, so meeting daily nutritional needs is not optimal. With this problem, we conducted community service using the counseling method for housewives, which is one of the efforts we can make to provide insight into the importance of healthy living and family nutrition in a good and correct way. The counseling was conducted for 5 days by carrying 5 materials in this counseling, namely toga plants, contents of my plate, 10 guidelines for balanced nutrition, stunting, and sanitation. Then, on the last day, we also evaluated by reviewing the material to find out whether the housewives in Jetis understood the material that had been delivered. From this counseling, we concluded that 85% of housewives in Jetis Village understand what we conveyed, and we hope they can apply it in their daily lives.